2010
DOI: 10.1111/j.1365-313x.2010.04330.x
|View full text |Cite
|
Sign up to set email alerts
|

A central role for gamma-glutamyl hydrolases in plant folate homeostasis

Abstract: SUMMARYMost cellular folates carry a short poly-c-glutamate tail, and this tail is believed to affect their efficacy and stability. The tail can be removed by c-glutamyl hydrolase (GGH; EC 3.4.19.9), a vacuolar enzyme whose role in folate homeostasis remains unclear. In order to probe the function of GGH, we modulated its level of expression and subcellular location in Arabidopsis plants and tomato fruit. Three-fold overexpression of GGH in vacuoles caused extensive deglutamylation of folate polyglutamates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Most cellular folates carry a short poly-γ-Glu tail, which is believed to affect their efficacy and stability. The tail can be removed by γ-glutamyl hydrolase (GGH), a vacuolar enzyme who has an important influence on polyglutamyl tail length and hence on folate stability and cellular folate content [19]. Folylpolyglutamate derivatives are central cofactors for many folate-dependent enzymes [20], [21], [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Most cellular folates carry a short poly-γ-Glu tail, which is believed to affect their efficacy and stability. The tail can be removed by γ-glutamyl hydrolase (GGH), a vacuolar enzyme who has an important influence on polyglutamyl tail length and hence on folate stability and cellular folate content [19]. Folylpolyglutamate derivatives are central cofactors for many folate-dependent enzymes [20], [21], [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, temperature extremes, high light levels, pH excursions, and stress-driven accumulations Table I. of metabolites with which cofactors react all directly accelerate diverse types of spontaneous cofactor damage (Treadwell and Metzler, 1972;Baggott, 2000;Mills et al, 2006;Marbaix et al, 2011). Abiotic stresses can also promote cofactor damage indirectly by altering compartmentation (Akhtar et al, 2010;Mohammadi et al, 2012) by inducing enzymes that break down cofactors (Rapala-Kozik et al, 2008;Higa et al, 2012) and by creating harsh cellular conditions in which enzymes that normally act on other substrates become more promiscuous (Piedrafita et al, 2015) and mistakenly attack cofactors. Figure 1 uses color-coded arrows to show the site and nature of damage reactions that vitamins and cofactors can undergo in physiological conditions, and Table I catalogs the reactions corresponding to the arrows.…”
Section: Chemical and Metabolic Lability: Why Bad Things Happen To Gomentioning
confidence: 99%
“…The cellular function of polyglutamylation remains unclear, although work has suggested that it plays a role in the stability, cellular retention, enzyme specificity, and homeostasis of folates (53,54). It is possible that 5-CHO-H 4 PteGlu n serves as a folate reserve that contributes to bacterial survival of folate antagonism.…”
Section: Discussionmentioning
confidence: 99%